2018
DOI: 10.1371/journal.pone.0201885
|View full text |Cite
|
Sign up to set email alerts
|

Will open access increase journal CiteScores? An empirical investigation over multiple disciplines

Abstract: This paper empirically studies the effect of Open Access on journal CiteScores. We have found that the general effect is positive but not uniform across different types of journals. In particular, we investigate two types of heterogeneous treatment effect: (1) the differential treatment effect among journals grouped by academic field, publisher, and tier; and (2) differential treatment effects of Open Access as a function of propensity to be treated. The results are robust to a number of sensitivity checks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 51 publications
2
22
0
1
Order By: Relevance
“…Studies in the field of oncology [6] and dentistry [7] found conflicting results. A recent study showed a higher citation rate for open access journals in general, but the effect was not uniform across different types of journals [8]. A recent study among radiology journals found no statistically significant differences in journal impact measures (including number of journal citations and impact factors) between journals with and without open access options [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the field of oncology [6] and dentistry [7] found conflicting results. A recent study showed a higher citation rate for open access journals in general, but the effect was not uniform across different types of journals [8]. A recent study among radiology journals found no statistically significant differences in journal impact measures (including number of journal citations and impact factors) between journals with and without open access options [4].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the easy access to knowledge in OA journals, the articles here have increased the IFs of the journals that are published with more citations. [9] The SJR indicator is calculated in a sophisticated manner by evaluating different data according to journal IF. Many different points are considered in the calculation of the journal IF and SJR indicator.…”
Section: Discussionmentioning
confidence: 99%
“…For journals that follow the open access policy, access to their content does not require a prior subscription; however, authors who decide to publish in them must pay an article processing charge. On the other hand, the magnitude of the increase in journal citations will depend on the characteristics of the journal, such as its field, range, and discipline, as well as trends in similar journals toward open access [101]. A: number of articles; TC: total citations for all articles; TC/A: number of citations per article; Ha: Hirsch-index in this topic; Hj: Hirsch-index in journal; SJR (Q): Scimago Journal Rank (Quartile); R: rank position by the number of articles published; OA: Open Access journal; NOA: Non-Open Access journal (include hybrid model).…”
Section: Identification Of the Most Prolific Journalsmentioning
confidence: 99%